2009
DOI: 10.1073/pnas.0908980106
|View full text |Cite
|
Sign up to set email alerts
|

Distributions of observed death tolls govern sensitivity to human fatalities

Abstract: How we react to humanitarian crises, epidemics, and other tragic events involving the loss of human lives depends largely on the extent to which we are moved by the size of their associated death tolls. Many studies have demonstrated that people generally exhibit a diminishing sensitivity to the number of human fatalities and, equivalently, a preference for risky (vs. sure) alternatives in decisions under risk involving human losses. However, the reason for this tendency remains unknown. Here we show that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(82 citation statements)
references
References 41 publications
5
77
0
Order By: Relevance
“…Overall, the management researchers in our sample are not in favor of inviting more co-authors: In none of the 10 scenarios did willingness to invite additional co-authors significantly exceed the "indifferent" category (i.e., the midpoint of "3" on the 1-5 scale). number of authors on their manuscript with the typical numbers they observe within their field (Olivola & Sagara, 2009;Stewart, Chater, & Brown, 2006). Single-authored, dual-authored, and tri-authored papers are all fairly common within the field of management (within our dataset, they represent, respectively, 42%, 31%, and 18% of the management articles published between 2003 and 2012), so having up to three authors on a manuscript may not seem like a particularly unusual or large number.…”
Section: Willingness To Invite Additional Co-authors: Preferences Andmentioning
confidence: 99%
“…Overall, the management researchers in our sample are not in favor of inviting more co-authors: In none of the 10 scenarios did willingness to invite additional co-authors significantly exceed the "indifferent" category (i.e., the midpoint of "3" on the 1-5 scale). number of authors on their manuscript with the typical numbers they observe within their field (Olivola & Sagara, 2009;Stewart, Chater, & Brown, 2006). Single-authored, dual-authored, and tri-authored papers are all fairly common within the field of management (within our dataset, they represent, respectively, 42%, 31%, and 18% of the management articles published between 2003 and 2012), so having up to three authors on a manuscript may not seem like a particularly unusual or large number.…”
Section: Willingness To Invite Additional Co-authors: Preferences Andmentioning
confidence: 99%
“…It may be that individuals regularly construct their preferences from a fairly stable memory cache (Olivola and Sagara 2009;Stewart et al 2006). This consistency is stronger for the simpler (1-parameter) models and weakest for the second-price auction.…”
Section: Model (Specification)mentioning
confidence: 99%
“…However, research has shown that we seem to evaluate the seriousness of deadly events by comparing their potential death tolls with those of other deadly events (Olivola & Sagara, 2009), rather than in terms of their absolute magnitudes. Thus, a deadly event will seem particularly shocking to us if its potential death toll is larger than most of the other death tolls we have observed (e.g., from watching the news).…”
Section: Reactions To Human Fatalities Are Fundamentally Relativementioning
confidence: 99%